Building audit in toilet facilities in UiTM Shah Alam / Muhammad Saiful Adli Kamaruddin - Kamaruddin, Muhammad Saiful Adli (Faculty of Architecture , Planning and Surveying, 2015)
Building Audit is the key to determine the level of maintenance and management of the building. Some organization has different policies and guidelines for their maintenance of toilet facilities. Building Audit in toilet facilities is to determine the level of it services compare to the current standard. This research is to determine the toilet provide the in UiTM about the audit in toilet facilities. The objective is to determine whether the toilet in UiTM is keep to standard toilet as should provide. It also measure the level service of facilities provided from the satisfactory of user. The aim is to improve the toilet facilities and management in UiTM Shah Alam. From this the research readers know the satisfactory level from the user of using the toilet through the questionnaire that are distribute into student and staff of UiTM and also know the condition of the facility provided inside the toilet through observation. The data is analyzed and the conclusion is made up from the result of user feedback and observation of real situation. The result show the rating that are calculated based on condition of facilities provided, common defect such as malfunction,cracking or unclean facilities and user satisfactory toward the facilities provided inside the toilet. These researches give information to the user and management about the current condition of the toilet and satisfactory of user toward the service provided. The management can use this research as their guideline for the better in providing the toilet facilities to the student and staff of UiTM.